An Exploration of Causes for Delay and Cost Overruns In Construction Projects: Case Study of Australia, Malaysia & Ghana - Shah, Raj Kapur (Journal of Advanced College of Engineering and Management, 2016)
Cost and time overruns are the key problems of any construction projects. These issues are causing the negative impact on the development of country economic growth and prosperity. To overcome these issues, the paper is aimed to discover the most influence factors causing the project delay and cost overruns and recommend the possible measures by investigating case studies in three different countries in the world. Each country’s quantitative data from the past studies was selected to analyze and recommend the effective measures. A questionnaire survey was conducted in all three case studies adopting different data collection strategy. The reason of selecting three case studies is to outline the compare analysis of delay factors and to classify why different delay factors have different priority level of influence in project delay from one country to another country. The findings from the case studies exposed that the most influential factors in Australia are (1) planning and scheduling deficiencies, (2) methods of construction, (3) effective monitoring and feedback process, whereas in Ghana, (1) delay in payment certificates (2) underestimating of project cost, (3) complexity of projects are the most influential factors. However, in Malaysia (1) Contractor’s improper planning, (2) poor site management, (3) inadequate contractor experience are the most influential factors. This paper has also analysed the average and least impact of the delay factors causing project delay and cost overruns in those countries. The paper concludes that there are diverse groups of delay factors from one country to another country that causing project delay and cost overruns. It also concludes that there are diverse measures according to the nature of delay factors to reduce the impact on project delay and cost overruns in construction industry. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, Page: 41-55